Factors that contribute towards the effectiveness of training among academicians / Wan Maziah Wan Ab Razak, Syahrul Nadwani Abdul Rahman and Kartini Mat Rashid - Wan Ab Razak, Wan Maziah; Abdul Rahman, Syahrul Nadwani; Mat Rashid, Kartini (2012)
The research is conducted to study the factors that contribute to the effectiveness of training among lecturers in UiTM Terengganu. This research will be focused only on the general types of training provided by departments of llqam Terengganu and Training unit to all the lecturers such as important training like basic teaching and learning workshop, research training, writing workshop, ICT Training, e-Learning and etc. From this research, the relationship among all factors that contribute towards the training provided for the lecturers in UiTM Terengganu will be found out. Besides, it is also to investigate the effectiveness of training to all lecturers. Sampling that will be used in which approximately 200 lecturers in the campus will become the subject of the study. The respondents will be all of the permanent lecturers in UiTM Terengganu, Dungun campus. Hopefully, after implementing this study it will help the organization to improve their training. Thus, to enhance the quality of training for the lecturers. The findings of this study can be in considered as continuous improvement on training in the organization. The top management would have another insight and knowledge of the impact of implementation of training practices on their employees. Moreover, the results of the study would be of significant value to organization that could use them as a useful reference to provide efficient training for the staff.